2013
DOI: 10.1177/193229681300700620
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Performance of Rapid-Acting Insulin Analogs Used for Continuous Subcutaneous Insulin Infusion: A Systematic Review

Abstract: Based on a limited amount of available data, the safety, stability, and performance of the three available rapid-acting insulin analogs available for use with CSII were similar. However, there is limited evidence suggesting that the risk of occlusion may vary with the insulin preparation under certain circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 33 publications
0
38
0
3
Order By: Relevance
“…Data in this area are limited and conflicting. While some studies show all insulins are relatively stable in CSII, maintaining their potency and stability [17,21,23], in a number of others, insulin aspart has been reported to have the lowest rate of occlusion, when compared to lispro and glulisine [14,24]. Another study suggests that insulin glulisine has an increased risk of precipitation and fibrillation compared with insulin aspart [21].…”
Section: Occlusionmentioning
confidence: 95%
See 1 more Smart Citation
“…Data in this area are limited and conflicting. While some studies show all insulins are relatively stable in CSII, maintaining their potency and stability [17,21,23], in a number of others, insulin aspart has been reported to have the lowest rate of occlusion, when compared to lispro and glulisine [14,24]. Another study suggests that insulin glulisine has an increased risk of precipitation and fibrillation compared with insulin aspart [21].…”
Section: Occlusionmentioning
confidence: 95%
“…While some studies show all insulins are relatively stable in CSII, maintaining their potency and stability [17,21,23], in a number of others, insulin aspart has been reported to have the lowest rate of occlusion, when compared to lispro and glulisine [14,24]. Another study suggests that insulin glulisine has an increased risk of precipitation and fibrillation compared with insulin aspart [21]. Supporting this, a 2008 study found that glulisine had significantly higher rates of occlusion than lispro or aspart when catheters were used for more than 72 h and emphasised the importance of frequent catheter changes (within 72 h) to minimise this risk [25].…”
Section: Occlusionmentioning
confidence: 99%
“…Fine-tuning alert settings can enhance CGM utility, but may not reduce the social burden of having attention called to the CGM user’s T1D. Many studies have documented the technical difficulties that individuals with T1D experience using insulin pumps including software problems, key pad failure/problem, battery issues, cracked/physical damage, insulin leaks, and set/site failures including occlusion [76, 8184]. Although overall discontinuation rates for insulin pump use were low in both the T1D Exchange Registry data (3%) and the DPV database (4%), reasons for discontinuation included problems with wearability (57%), disliking the pump and/or feeling anxious about it (44%), and problems with glycemic control (30%).…”
Section: Biopsychosocial Factors Associated With Cgm and Insulin Pumpmentioning
confidence: 99%
“…This is important in the management of diabetes because the onset and peak of rapid-acting insulin correspond to the time that postprandial glucose levels spike (Weissman, n.d.), thus preventing spikes and producing better HbA1c results, compared to short-acting insulin (Brown, 2012). Differences between the three rapid-acting insulin analogs in terms of glycemic control and, ultimately, HbA1c reduction was systematically reviewed by Kerr, Wizemann, Senstius, Zacho, and Ampudia-Blasco (2013); this review did not suggest any statistical differences in effectiveness between the three rapid-acting analogs. Of significance, all rapid-acting insulin used in CSII is shown to mimic the body's natural response to mealtime and basal secretion (Kerr et al, 2013).…”
Section: Rapid-acting Insulinmentioning
confidence: 99%
“…Differences between the three rapid-acting insulin analogs in terms of glycemic control and, ultimately, HbA1c reduction was systematically reviewed by Kerr, Wizemann, Senstius, Zacho, and Ampudia-Blasco (2013); this review did not suggest any statistical differences in effectiveness between the three rapid-acting analogs. Of significance, all rapid-acting insulin used in CSII is shown to mimic the body's natural response to mealtime and basal secretion (Kerr et al, 2013). Furthermore, when rapid-acting and short-acting insulins were compared in CSII therapy, rapid-acting analogs demonstrated a greater reduction in HbA1c than short-acting (Brown, 2012).…”
Section: Rapid-acting Insulinmentioning
confidence: 99%